Genomic Survey, Characterization, and Expression Profile Analysis of the SBP Genes in Pineapple (Ananas comosus L.). (29th September 2017) - Ali, Hina; Liu, Yanhui; Azam, Syed Muhammad; Rahman, Zia ur; Priyadarshani, S. V. G. N.; Li, Weimin; Huang, Xinyu; Hu, Bingyan; Xiong, Junjie; Ali, Umair; Qin, Yuan
Abstract : Gene expression is regulated by transcription factors, which play many significant developmental processes. SQUAMOSA promoter-binding proteins (SBP) perform a variety of regulatory functions in leaf, flower, and fruit development, plant architecture, and sporogenesis. 16 SBP genes were identified in pineapple and were divided into four groups on basis of phylogenetic analysis. Five paralogs in pineapple for SBP genes were identified with Ka/Ks ratio varied from 0.20 for AcSBP14 and AcSBP15 to 0.36 for AcSBP6 and AcSBP16, respectively. 16 SBP genes were located on 12 chromosomes out of 25 pineapple chromosomes with highly conserved protein sequence structures. The isoionic points of SBP ranged from 6.05 to 9.57, while molecular weight varied from 22.7 to 121.9 kD. Expression profiles of SBP genes revealed that AcSBP7 and AcSBP15 (leaf), AcSBP13, AcSBP12, AcSBP8, AcSBP16, AcSBP9, and AcSBP11 (sepal), AcSBP6, AcSBP4, and AcSBP10 (stamen), AcSBP14, AcSBP1, and AcSBP5 (fruit) while the rest of genes showed low expression in studied tissues. Four genes, that is, AcSBP11, AcSBP6, AcSBP4, and AcSBP12, were highly expressed at 4°C, while AcSBP16 were upregulated at 45°C. RNA-Seq was validated through qRT-PCR for some genes. Salt stress-induced expression of two genes, that is, AcSBP7 and AcSBP14, while in drought stress, AcSBP12 and AcSBP15 were highly expressed. Our study lays a foundation for further gene function and expression studies of SBP genes in pineapple.